(untitled) (Damascus University Journal of agriculture sciences, 2024)
This investigation was conducted in the laboratory of biotechnology affiliated to the Department of Field Crops, Faculty of Agriculture, Damascus University, during (2021) season, for Molecular characterization of some genotypes of sorghum (Aklamoni, Giza 15, Misr 9, Jazan Al Ahmar, Shalakh 6, jioue, Shahla, Tabit, Omani local) using Inter Simple Sequence Repeats technique ISSR.Twenty five ISSR primers were used for this purpose, The results showed that 16 primers were effective in showing polymorphism between the examined sorghum genotypes. The primers gave 81 bands 69 of them were polymorphic, with a polymorphism percentage of 87.32 %. the number of bands for each primer ranged from 2 bands for the primer ISSR36 to 12 bands for the primer ISSR17with an average of 5.1 bands. The PIC was calculated for each primer separately, and the average was 0.42. It was observed that the lowest value of PDV was 0.092 between the two genotypes Misr9 and Giza15 (which are from Egypt), as well as between the two genotypes Tabit and Aklamoni (both from Sudan), while the highest value of PDV was 0.693 between the two genotypes, Shalakh6 (Syria) and Jazan Al-Ahmar (Saudi Arabia), which indicates a large genetic variation between them. They were followed by the genotypes Shalekh 6, Tabit and Aklamoni with a PVD value of 0.664. Cluster analysis divided the nine genotypes into two main clusters, the first cluster included Shalekh 6 which is the farthest, and the second cluster included the others,Which was divided into two sub clusters, the first one included local Omani while the second included Jazan and Shahla, and the two genotypes Egypt 9 and Giza15 were the closest genetically. So, the studied genotypes were separated according to their geographical distribution, which indicates the effectiveness of the ISSR technique in probing the genetic variation between sorghum genotypes.